Production Process Technology of Lecithin from Crude Palm Oil on The Physico Chemical Properties of Halal Dark Chocolate produced - Latief, Madyawati; Nizori, Addion; Rahmi, Silvi Leila; Nabila, Annisa Candra; Tarigan, Indra Lasmana; Huda, Nurul; Yusof, Yus Aniza (Indonesian Food Science and Technology Journal, 2023)
This research was conducted to determine the effect of the addition of CPO (Crude Palm Oil) lecithin as an Emulsifier on the physicochemical and sensory characteristics of dark chocolate, and to determine the amount of lecithin addition as an appropriate Emulsifier to produce chocolate with the best physico-chemical and sensory characteristics. This study used a completely randomized design (CRD) method with a treatment level of 0%. 0.1%, 0.2%, 0.3%, 0.4% with 4 repetitions to obtain 20 experimental units. Parameters observed included color degee, antioxidant activity, fat blooming, stability level, color sensory test, taste, aroma, texture and overall acceptability. The data obtained were analyzed using ANOVA levels of 1% and 5%. If there is a significant effect on the treatment, it will be continued with the Duncan's Multiple Range Test (DNMRT) at the 5% level. The best concentration of adding lecithin to dark chocolate is 0.3% which contains 66.76% antioxidant activity, color degee L*28.58, a* 13.67, b* 22.67, hue 58.75, good stability (melting properties), able to prevent fat blooming, has good color very chocolatey (4.20), very distinctive aroma of chocolate (4.44), bitter taste (2.68), smooth texture (3.36) and the overall acceptance of the panelists really liked it (8.16).